IMPLEMENTASI KEYAKINAN KELAS DALAM MENUMBUHKAN MOTIVASI BELAJAR SISWA SMP NEGERI 4 SUNGAI KAKAP - Sofwatul Umah (Jurnal Pendidikan Edukasi Kusuma Bangsa, 2025)
This research aims to describe the implementation of classroom beliefs in fostering learning motivation for class IX students at SMP Negeri 4 Sungai Kakap. Classroom beliefs include the values, rules, and expectations agreed upon by teachers and students as guidelines for the learning process. This research uses a qualitative method with a descriptive approach. Data collection was carried out through observation, interviews with students, and distribution of questionnaires to measure student learning motivation. Aspects of learning motivation that are measured include interest in learning, effort and perseverance, as well as a conducive learning environment. The research results show that consistent implementation of classroom beliefs is able to foster student interest in the subject matter, strengthen effort and persistence in completing assignments, and create a learning environment that supports student comfort and active participation. Supporting factors in classroom implementation are the teacher's commitment to implementing classroom beliefs, a conducive learning environment, and peer support. The factors inhibiting the implementation of classroom beliefs are the lack of consistency between teachers and students in implementing classroom beliefs and the lack of student awareness of the importance of classroom beliefs. This research recommends strengthening communication between teachers and students to further optimize the application of classroom beliefs in order to increase learning motivation.